Effective splicing restoration of a deep-intronic ABCA4 variant in cone photoreceptor precursor cells by CRISPR/SpCas9 approaches - Pietro De Angeli; Peggy Reuter; Stefan Hauser; Ludger Schöls; Katarina Stingl; Bernd Wissinger; Susanne Kohl (Elsevier, 2022)
Stargardt disease is an autosomal recessively inherited retinal disorder commonly caused by pathogenic variants in the ABCA4 gene encoding the ATP-binding cassette subfamily A member 4 (ABCA4) protein. Several deep-intronic variants in ABCA4 have been classified as disease causing. By strengthening a cryptic splice site, deep-intronic variant c.5197-557G>T induces the inclusion of a 188-bp intronic sequence in the mature mRNA, resulting in a premature termination codon. Here, we report the design and evaluation of three CRISPR-Cas9 approaches implementing Streptococcus pyogenes Cas9 (single and dual guide RNA) or Streptococcus pyogenes Cas9 nickase (dual guide RNA) for their potential to correct c.5197-557G>T-induced aberrant splicing in minigene splicing assays and patient-derived cone photoreceptor precursor cells. The different strategies were able to rescue correct splicing by up to 83% and increase the overall correctly spliced transcripts by 1.8-fold, demonstrating the successful CRISPR-Cas9-mediated rescue in patient-derived photoreceptor precursor cells of an ABCA4 splicing defect. The results provide initial evidence of possible permanent splicing correction for Stargardt disease, expanding the therapeutic toolbox to counteract deep-intronic pathogenic variants in ABCA4.